(untitled) (Al-Academy, 2024)
The entitled research (Features of Popular Heritage in Contemporary Iraqi Painting) consists of four chapters. The first chapter includes the research problem, importance, objectives, and limits, while the second chapter includes the theoretical framework that contains two sections: The first section: Popular heritage (characteristics and features) and the second section: The role of popular heritage in contemporary Iraqi formation. The third chapter included the research procedures and analysis of the research sample, while the fourth chapter included the research results, the most important of which were: Iraqi painters invest themes or symbols of their popular heritage in their artistic works. The diversity of materials and raw materials in the paintings of Iraqi painters. The diversity of performance of Iraqi painters in their artistic works